Three-Dimensional Integration and Modeling A Revolution in RF and Wireless Packaging - Lee, Jong-Hoon; Tentzeris, Manos M. (Synthesis Lectures on Computational Electromagnetics, 2008)
This book presents a step-by-step discussion of the 3D integration approach for the development of compact system-on-package (SOP) front-ends.Various examples of fully-integrated passive building blocks (cavity/microstip filters, duplexers, antennas), as well as a multilayer ceramic (LTCC) V-band transceiver front-end midule demonstrate the revolutionary effects of this approach in RF/Wireless packaging and multifunctional miniaturization. Designs covered are based on novel ideas and are presented for the first time for millimeterwave (60GHz) ultrabroadband wireless modules. Table of Contents: Introduction / Background on Technologies for Millimeter-Wave Passive Front-Ends / Three-Dimensional Packaging in Multilayer Organic Substrates / Microstrip-Type Integrated Passives / Cavity-Type Integrated Passives / Three-Dimensional Antenna Architectures / Fully Integrated Three-Dimensional Passive Front-Ends / References.